TikTok and Gendered Romantic Expectations: a Qualitative Study of College Students - Ceria, Regitha Ayu Anaristi; Azzahra, Zareta (Jurnal Bahasa, Sastra, dan Studi Amerika, 2000)
As TikTok continues to gain popularity for its short-form videos, romance-related content has become a prominent genre, often promoting specific ideals and norms in romantic relationships. This study analyzes the influence of TikTok on shaping romantic expectations among male and female users. Using a qualitative approach, this research involved semi-structured interviews with young adults who actively engage with romance-themed TikTok content. The findings reveal that male participants highly maintained traditional views of masculinity and financial responsibility, such as the expectation to be the primary provider, before and after consuming such content. Female participants, meanwhile, experienced more noticeable shifts in expectations—holding flexible and realistic views on romance, but later expressing greater desire for visible emotional and financial investment from partners. Despite these influences, both genders demonstrated critical engagement with the content, often distinguishing between social media ideals and real-life relationship values. This research emphasizes TikTok’s dual role as a platform that both strengthens and challenges traditional gender norms in romantic contexts. While some creators show how men should not share their emotional vulnerability, others challenge these norms by promoting emotional openness between men and their partners. Users, in turn, selectively compare these portrayals in line with their personal experiences.